Two-Dimensional Imaging Algorithm Based on Linear Prognosis for Space Target in Bistatic ISAR System - Xueping Lu; Shapu Ren (Universitas Ahmad Dahlan, 2014)
In bistatic inverse synthetic aperture radar (Bi-ISAR) system, its image resolution is lower than monostatic ISAR system. In order to solve this problem, the linear prognosis algorithm is adopted in the imaging process and the imaging algorithm based on linear prognosis is proposed. Space target Bi-ISAR imaging is taken as example in the research. The one-dimensional range profile is created through pulse compression method. Before the azimuth compression, burg entropy maximum algorithm in Levions recursive method is used to estimate the prognosis coefficients and the azimuth echo data. Then Fourier transformation is used to compress the azimuth data in order to get the high resolution azimuth image. This imaging method can obtain the two-dimensional image with the resolution equal to the monostatic ISAR or even higher than it. Simulation experiments have verified the effectiveness and availability of the algorithm.